How short-term variation influence the relative importance of environmental and spatial factors associated to anuran dissimilarity composition - Mello, Flávia Gomes de (Universidade Federal de São Carlos, 2018)
Understanding the processes that create the patterns of species composition and biodiversity variation across the space has been one of the main topics within the theory of metacommunities. However, most studies rely on static snapshots of community data and few studies have examined the importance of including temporal variability. Here, we examined beta diversity distribution of anuran community composition through three years and considering the whole period of study at different spatial extents in the Brazilian Atlantic Forest: i) seven inland communities; ii) seven coastal communities; and iii) communities pooled together. We partitioned total beta diversity into species replacement and nestedness-resultant components then we used deviance partitioning to explore the relative importance of environmental and spatial factors explaining the distribution of anuran community changes over the years. Species replacement was the predominant component of anuran beta diversity, but average values of species replacement and nestedness-resultant were not congruent across the years. We observed that average values of beta diversity components decrease when species composition of whole period of study are pooled together and increase with increasing spatial extent. Furthermore, our results indicate that Brazilian Atlantic Forest anuran community compositions are highly dynamic in space and time, and the factors explaining the distribution of species replacement and nestedness-resultant are dependent of the sampling year and spatial extent. Thus, metacommunity studies that do not evaluate different spatial and temporal changes should be cautious about the generality of their biological conclusions.
Keywords: Montagem de comunidades; Aninhamento; Substituição de espécies; Diversidade temporal; Partição da variância; Community assembly; Nestedness-resultant; Species replacement; Temporal diversity; Variation partitioning; CIENCIAS BIOLOGICAS::ECOLOGIA